A Lipidomic Signature Complements Stemness Features Acquisition in Liver Cancer Cells - Rivas Serna, Irma Magaly; Romito, Ilaria; Maugeri, Andrea; Lo Re, Oriana; Giallongo, Sebastiano; Mazzoccoli, Gianluigi; Oben, Jude A; Li Volti, Giovanni; Mazza, Tommaso; Alisi, Anna; Vinciguerra, Manlio (International journal of molecular sciences, 2020)
Lipid catabolism and anabolism changes play a role in stemness acquisition by cancer cells, and cancer stem cells (CSCs) are particularly dependent on the activity of the enzymes involved in these processes. Lipidomic changes could play a role in CSCs' ability to cause disease relapse and chemoresistance. The exploration of lipid composition and metabolism changes in CSCs in the context of hepatocellular cancer (HCC) is still incomplete and their lipidomic scenario continues to be elusive. We aimed to evaluate through high-throughput mass spectrometry (MS)-based lipidomics the levels of the members of the six major classes of sphingolipids and phospholipids in two HCC cell lines (HepG2 and Huh-7) silenced for the expression of histone variant macroH2A1 (favoring stemness acquisition), or silenced for the expression of focal adhesion tyrosine kinase (FAK) (hindering aggressiveness and stemness). Transcriptomic changes were evaluated by RNA sequencing as well. We found definite lipidomic and transcriptomic changes in the HCC lines upon knockdown (KD) of macroH2A1 or FAK, in line with the acquisition or loss of stemness features. In particular, macroH2A1 KD increased total sphingomyelin (SM) levels and decreased total lysophosphatidylcholine (LPC) levels, while FAK KD decreased total phosphatidylcholine (PC) levels. In conclusion, in HCC cell lines knocked down for specific signaling/epigenetic processes driving opposite stemness potential, we defined a lipidomic signature that hallmarks hepatic CSCs to be exploited for therapeutic strategies.
Keywords: regulace genové exprese u nádorů; Lipidomics; Hep G2 Cells; buňky Hep G2; Cell Line, Tumor; hepatocelulární karcinom; sfingomyeliny; Gene Expression Regulation, Neoplastic; sekvenování transkriptomu; fokální adhezní kinasa 1; nádorové buněčné linie; Focal Adhesion Kinase 1; lidé; Gene Knockdown Techniques; nádory jater; Carcinoma, Hepatocellular; Lipid Metabolism; fosfatidylcholiny; stanovení celkové genové exprese; metabolismus lipidů; Sphingomyelins; Phosphatidylcholines; Liver Neoplasms; nádorové biomarkery; lipidomika; Neoplastic Stem Cells; genový knockdown; Lysophosphatidylcholines; Biomarkers, Tumor; histony; Histones; RNA-Seq; lysofosfatidylcholiny; Gene Expression Profiling; nádorové kmenové buňky; Humans